2015
DOI: 10.1111/1365-2435.12596
|View full text |Cite
|
Sign up to set email alerts
|

Cushion plant morphology controls biogenic capability and facilitation effects of Silene acaulis along an elevation gradient

Abstract: 1. The stress-gradient hypothesis (SGH) predicts that the balance of plant-plant interactions shifts along abiotic environmental gradients, with facilitation becoming more frequent under stressful conditions. However, recent studies have challenged this perspective, reporting that positive interactions are, in some cases, more common at the intermediate level of environmental severity gradients. Here, we test whether and how neighbour effects by Silene acaulis cushions vary along a 700 m wide altitudinal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 60 publications
6
84
1
Order By: Relevance
“…Overall, we found that species diversity and richness within and next to cushions is lower compared to control areas, indicating net competitive interactions between cushions and other plant species (Figure ). Such negative or neutral interactions have been documented in other studies as well (e.g., de Bello et al., ; Dvorsky et al., ; Bowman & Swatling‐Holcomb, ), but surprised us given that Silene has been shown to increase species percent cover and richness (Bonanomi et al., ). Although disturbance reduces both species richness and diversity, it has no effect on species interactions, as measured by RII.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Overall, we found that species diversity and richness within and next to cushions is lower compared to control areas, indicating net competitive interactions between cushions and other plant species (Figure ). Such negative or neutral interactions have been documented in other studies as well (e.g., de Bello et al., ; Dvorsky et al., ; Bowman & Swatling‐Holcomb, ), but surprised us given that Silene has been shown to increase species percent cover and richness (Bonanomi et al., ). Although disturbance reduces both species richness and diversity, it has no effect on species interactions, as measured by RII.…”
Section: Discussionsupporting
confidence: 58%
“…The cushion plant Silene has been found to host an increasing number of species at higher elevations (Antonsson, Björk, & Molau, ), while also demonstrating greatest facilitative effects on other species at the center of its elevational range (Bonanomi et al., ) as well as in abiotically stressful environments (Kjaer, Olsen, & Klanderud, ). We therefore expected cushion plants to first, host higher species diversity and richness compared to control areas, and second, maintain this higher diversity in areas where disturbance exerts negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in alpine systems have documented contrasting effects of different phenotypes of foundation species on subordinate species (Al Hayek, Maalouf, Touzard, & Michalet, ; Al Hayek, Touzard, Le Bagousse‐Pinguet, & Michalet, ; Al Hayek et al., ; Bonanomi et al., ; Michalet, Maalouf, & Hayek, ; Michalet et al., ). However, the mechanisms underlying these effects are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…(), Bonanomi et al. (), and Jiang et al. () stressed the importance of above‐ground traits—in particular canopy compactness—to explain the negative effects of tight phenotypes as compared to loose ones on associated species, although Schöb et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the variability of shapes in the stress–interaction relationship observed in the field remains detrimental to the generalization of the SGH (reviewed by Soliveres et al ). One flagship example of these discrepancies is the facilitation collapse or the stabilization of facilitative effects by nurses observed at the extremity of aridity gradients (Michalet et al ) but also possibly at the extremity of alpine gradients (Dvorsky et al , Bonanomi et al ).…”
mentioning
confidence: 99%